Clinical Characteristics and Treatment Outcomes Among Patients With Gastrointestinal Phytobezoars: A Single-Institution Retrospective Cohort Study in Korea - Yang, Songsoo; Cho, Min Jeng (Frontiers in Surgery, 2021)
Purpose: To describe our experience with phytobezoars, evaluate risk factors on treatment, and analyze whether previous gastric surgery affects treatment outcomes. Methods: Medical records of 51 patients with phytobezoars between 2000–2019 were retrospectively evaluated. We compared endoscopic and surgical treatment groups and evaluated risk factors using multivariate logistic regression analysis. And we compared patients with and without previous gastric surgery in the surgical treatment group. Results: The median patient age was 62.9 (range: 27-89) years. The endoscopic and surgical treatment groups included 26 (51%) and 25 (49%) patients, respectively. Patients aged ≥65 years, diabetes, and small intestinal phytobezoars were more frequent in the surgical treatment group. Previous gastric surgery (n=16, 31.4%) was the most common predisposing risk factor, but without a significant difference between the groups. Enterotomy was performed for 20 patients (80%), segmental resection was performed for five patients (20%). Five patients (20%) had postoperative complications; there was one death. There were no significant differences in age, preoperative diagnosis, operation method, operative time, or postoperative stay between patients with and without previous gastric surgery, but postoperative complications were significantly more common in patients with previous gastric surgery. Conclusions: Phytobezoar should be suspected early in patients with previous gastric surgery or a specific food intake history. Early diagnosis and treatment are important for avoiding surgical intervention and complications, especially in elderly patients. Surgery is required in most patients with small intestinal phytobezoars, safe removal can be achieved mainly via enterotomy.